Carnival, Power, and Queer Joy: Chrono-normativity, Carnivalesque Transgressions, and the Spectacle of Gender in Lourenço Marques, Mozambique (ca. 1950–1975) - Araújo, Caio (Nordic Journal of African Studies, 2023)
This article is an exploratory study of the history of carnival as a popular festival in late colonial Lourenço Marques (contemporary Maputo), the capital of Mozambique. Drawing on archival sources and on oral history interviews, it explores the carnival as a site of struggle, shaped by attempts at regulation by the state and co-optation by private capital, but also critically positioned as a potential space of freedom, joy, and experimentation. Looking at instances of racial, sexual, or gender transgression within it, the article presents the festival as an ambivalent, contradictory assemblage of practices and political dispositions, in which desire for subversion and play rubbed up – just as much as the bodies of carnival goers – against the policing of the colonial boundaries of race, gender, class, and sexuality. The article also maps out carnival’s transnational attachments, following the circulation of people, practices, and cultural forms in the Lusophone world. The case of Brazilian travesti performers is explored as an instance of southern connectivity, allowing a reading of carnival as transnational queer culture. Working with various materials and themes, the article imagines what queer and gender histories may emerge if one focuses on moments of transgression and gender-bending and on those actions that destabilize and complicate dominant sexual cultures and normative gender regimes.